The synthesis of genre dominants of Robinsonade and Bildungsroman in the «Life of Pi» by Yann Martel (Literatures of the World: Poetics, Mentality and Spirituality, 2018)
The article deals with the features of Robinsonade and Bildungsroman in «Life of Pi» (2001) by modern Canadian writer Yann Martel. The functioning of motives of isolation, island, survival, the struggle of natural and civilizational foundations in human consciousness, on the one hand, and motives of growing up and formation of a social model of behavior – on the other – are studied on the material of the text. Also, the role of religious ideas in the worldview of the character is revealed. The author accentuated the unity of the dominants of two classical genres in the novel.
Keywords: Robinsonade; Bildungsroman; shipwreck; isolation; animal; island; survival; growing up; religion